Adjuvant Radiotherapy Versus Surveillance for Grade 2 Intracranial Meningiomas: A Multi-Institutional Propensity Score-Matched Study - Byun, Hwa Kyung; Chang, Won Ick; Lee, Joo Ho; Park, Chul-Kee; Kim, In Ah; Kim, Chae-Yong; Cho, Jaeho; Kim, Eui Hyun; Chang, Jong Hee; Kang, Seok-Gu; Moon, Ju Hyung; Lee, Sang Hyung; et al. (Frontiers in Oncology, 2022)
Purpose: We aimed to compare the outcomes of adjuvant radiotherapy (ART) and surveillance in patients with grade 2 meningiomas (MNG2) who underwent surgical resection. Materials and Methods: Data from four hospitals, in which patients aged ≥18 years underwent Simpson grade 1−4 surgical resection for newly diagnosed MNG2 between 1998 and 2018, were examined in this multicenter retrospective cohort study. Patients receiving ART with conventional fractionation were compared with those undergoing surveillance. Progression-free survival (PFS), progression/recurrence (P/R) were evaluated. Results: This study included 518 patients, 158 of whom received ART. The median follow-up duration was 64.9 months. In the total cohort, ART was independently associated with significantly improved PFS (HR, 0.35; 95% CI, 0.23–0.55; P<0.001) and P/R (HR, 0.30; 95% CI, 0.18–0.48; P<0.001). In the propensity score-matched cohort (n=143 in each group), the 5-year PFS rates were 80.8% and 57.7% (P=0.004), and the 5-year P/R rates were 16.5% and 40.0% (P=0.002) in the ART and surveillance groups, respectively. After gross total resection, the 5-year PFS (85.0% vs. 64.7%; P=0.020) and P/R rates (15.2% vs. 32.0%; P=0.035) were significantly better in the ART group than in the surveillance group. A model for P/R was developed using recursive partitioning analysis with surgical extent, tumor size, and Ki-67 index. ART reduced the risk of P/R in the low- (P=0.069), intermediate- (P=0.044), and high-risk groups (P<0.001). Local control was also significantly enhanced by ART among all the risk groups (all P<0.05). Conclusions: ART significantly improved PFS and P/R in patients with MNG2, irrespective of the surgical extent, and can be recommended after gross total resection. A prognostic model may guide decision-making for the use of ART.